Relationship Between Sleep Quality and Quality of Life with Nutritional Status and Cardiometabolic Risk in Physically Active Older Adults [Relación Entre Calidad de Sueño y Calidad de Vida Con el Estado Nutricional y Riesgo Cardiometabólico en Adultos Mayores Físicamente Activos] - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2018)
Introduction: The increase in the population of older adults is a global reality that poses great challenges and opportunities to societies. Objective: To relate sleep quality and the perception of quality of life with the nutritional status and cardiometabolic risk in Chilean physically active older adults. Material and method: Cross-sectional study that evaluated 212 older adults. We studied the Pittsburgh Sleep Quality Index, the Epworth Sleepiness Scale, the health-related quality of life SF-36, the nutritional status according to body mass index and the cardiometabolic risk according to waist circumference and waist-to-height ratio. Comparisons were made through the Student’s t-test and associations through logistic regression, considering p<0.05. Results: Older adults evaluated showed significant differences only among women for sleep latency (p=0.022). In addition, the logistic regression showed a relationships between lower sleep latency with a low probability of being overweight/obesity (OR=0.276, 95% CI=0.086-0.887, p=0.031). On the other hand, less sleep increases the probability of being overweight/obesity (OR=3.921, 95% CI=1.061-14.490, p=0,031). The dimensions of quality of life did not report significant relationships with nutritional status or cardiometabolic risk. Conclusions: Chilean older adults participating in physical activity governmental workshops that present greater sleep latency and less sleep exhibit a higher risk of being overweight/obesity. In addition, the perception of quality of life is positive regardless of their nutritional status or cardiometabolic risk. © 2018 Sociedad espanola de dietetica. All rights reserved.